Migration of pupils of boarding establishments from occupation areas: state, problems, perspectives - Lilia Yeromina (Problemy Wczesnej Edukacji)
The article is devoted to an analysis of the social-psychological state of pupils of boarding establishments that had to migrate. On the basis of practical experience of communication and work with pupils of boarding establishments the author of the article analyses the specific nature of giving social-pedagogical help to this category of children. The article’s problematic field is a description of the migration situation among pupils of boarding establishments in the conditions of occupation regime and specification of the perspectives of the future investigation in this topic.